Aplicación del modelo constructivista enfocado desde la teoría de Jerome Bruner (aprendizaje por descubrimiento) para mejorar el proceso de enseñanza aprendizaje en la asignatura de biología para primer año paralelo “a” del bgu del colegio “Manuel Ignacio Monteros Valdivieso - Marín Yumbla, Janneth Carolina (2020)
The following research, focused on the improvement of the teaching-learning process through the implementation of discovery-based learning method in the Biology area, is aimed at enhancing students’ cognitive skills to obtain a meaningful learning. An intervention plan was carried out to achieve this purpose, applying the inductive method, at Unidad Educativa “Manuel Ignacio Monteros”, among students in third year of bachillerato in Biology subject. Before the intervention plan implementation, it was necessary to stablish the principal issue by research techniques such as observation, survey and interviews with students and teachers, therefore, shortcomings were evidenced related to the methodology due to non-usage of didactive activities and recourses which provide students learning. As an alternative solution for this issue a proposal was settled, which, after being undertaken, helped to evidence, through the analytic method, its success. Since discovery-based learning allowed students to build their own knowledge and thus to keep a lasting learning. It was mainly observed regarding to students’ grades.